The Effect of Recruitment, Selection and Training on The Performance of Meeting The Quality Standards of The Uniqueness of Integrated Islamic Schools Mediated by Organizational Commitment - Ulin Ibrahim; Mulyadi Mulyadi; Asep Saifudin; Deni Gustiawan (Green Publisher Indonesia, 2025)
This study aims to determine and analyze the effect of recruitment, selection and training on the performance of meeting the quality standards of the uniqueness of integrated Islamic schools mediated by organizational commitment. This research includes quantitative research. The population in this study were 160 employees of SIT Al Ishlah Gorontalo. The sample in this study was 110 people who were determined based on the sample table by Isaac and Michael. This study uses a Structural Equation Model (SEM) approach with a measurement model using the Lisrel 8.80 program. The results of this study indicate that there is no influence between each recruitment and selection variable on organizational commitment or performance in fulfilling quality standards specific to SIT, there is an influence between training variables on organizational commitment and performance in fulfilling quality standards specific to SIT and there is an influence between each variable between each recruitment, selection and training variable on performance in fulfilling quality standards specific to SIT mediated by organizational commitment.